2004
DOI: 10.1097/00004032-200406000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intakes of Seven Elements of Importance in Radiological Protection by Asian Population: Comparison With Icrp Data

Abstract: Within the framework of a Coordinated Research Project (CRP) organized by the International Atomic Energy Agency, Vienna, the daily dietary intakes of seven elements by adult populations living in nine Asian countries were estimated. The countries that participated in the study were Bangladesh, China, India, Indonesia, Japan, Pakistan, Philippines, South Korea (Republic of Korea, ROK), and Vietnam and together they represented more than half of the world population. The seven elements studied were calcium, ces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 12 publications
1
13
1
3
Order By: Relevance
“…MED of daily iodine intake was 326.8 lg for China, 85.0 for India, 246.0 for Japan, 86.98 for the Republic of Korea, 43.47 for Pakistan, 30.0 for the Philippines, and 1449 for Vietnam. The high levels in China and Vietnam may be due to the use of iodized salt [18,19]. The median intake for other Asian countries was 90 lg/day which was lower than the values in this study and in other reports on Japan [7,[15][16][17]20].…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…MED of daily iodine intake was 326.8 lg for China, 85.0 for India, 246.0 for Japan, 86.98 for the Republic of Korea, 43.47 for Pakistan, 30.0 for the Philippines, and 1449 for Vietnam. The high levels in China and Vietnam may be due to the use of iodized salt [18,19]. The median intake for other Asian countries was 90 lg/day which was lower than the values in this study and in other reports on Japan [7,[15][16][17]20].…”
Section: Discussioncontrasting
confidence: 83%
“…As seaweeds have high iodine content [4], Japanese people can be expected to take in more iodine than people in other countries [14][15][16][17][18]. Tsukada et al [7] reported that Japanese students' intake of iodine from FCT-based data was 339 lg/day as MED, and Imaeda et al [15] calculated iodine intake of 312 and 413 lg/day as MED for men and women, based on the FCT values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In between these two dates, the NCRP (1 983) quoted a value of 100 d. Since people living in the developed countries of the world tend to have more readily available access to seafood (which contains relatively high quantities of stable iodine) and routinely consume iodized salt, it may well be that separate coefficients should be developed, depending on the amount of stable iodine being consumed by the population to whom the coefficients are being applied. This is confirmed by the fact that recent studies of populations in nine Asian countries, representing more than half of the world population, showed that their average total daily intake of stable iodine was only 90 pg, 45% of the ICRP value for Reference Man (Iyengar et al 2004). In these cases, the application of the ICRP coefficient would yield a dose estimate that is less than half of the correct value.…”
Section: Review and Commentarymentioning
confidence: 79%
“…A determinação da ingestão de minerais traço é importante não somente para avaliar o estado nutricional, mas também para estimar parâme-tros metabólicos de captação e deposição de radionuclídeos tais como Th e 238 U no corpo humano (CHO et al, 2001;IYENGAR et al, 2004).Medidas de radionuclídeos que ocorrem naturalmente no meio ambiente podem ser usadas não somente como referên-cia, quando são avaliados lançamentos de rotina de instalações nucleares ou exposição à radiação acidental, mas também como nível de base para avaliar o impacto causado por atividades não nucleares, tal como avaliação de impacto radiológico de fertilizantes fosfatados usados na agricultura. Estima-se que o uso desses fertilizantes tem pelo menos dobrado a exposição prolongada de seres humanos a partir da ingestão de alimentos, devido ao aumento de até uma ordem de magnitude ou mais, nos níveis de concentração de radionuclídeos em alimentos (ICRP, 1999).…”
unclassified